Vision and perspective of industrial engineering in management of organizations - Cachay Boza, Orestes (2012)
In the process of development of industrial engineering, it has been verified the importance of scientific management for business growth, contributing to the consolidation of the industrial clusters and developing nations, reaching Taylor’s target for economic development through business efficiency. Although industrial engineers have a high focus on results and improve of organizations, do not reach the success of other professions, which are focused on nonbusiness topics. The exploratory study aims to identify preliminarily, elements which, in front of requirement to occupy senior management positions in organizations, the stockholders tend to elect humanistic professions, such as lawyers, before the business professions such as industrial engineers. They have been identified the elements that define the preference stated. These are: a) method o solution analyticalreductionist against historicist-integrator, b) focus convergent approach on specific issues against divergent and wide approach, c) achievement as specific outcomes defined as short-term gains against long-term gains, d) hierarchy of problems with tangible resources and operational level variables versus social concepts and strategic level variables.